Manufacturing method of electrode laminate
Patent Information
- Application Number
- JP2023126328
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
【0011】 本開示の電極積層体の製造方法によると、ロールプレス直後に発生するシワを抑制することができる。
Smart Images

Figure 2025022085000002 
Figure 2025022085000003 
Figure 2025022085000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for manufacturing an electrode stack. [Background technology]
[0002] It is known that when manufacturing an electrode laminate, the electrode laminate is pressed by a roll press in order to increase the density of the electrode active material layer contained in the electrode laminate. When the electrode laminate is roll pressed, wrinkles and distortions may occur in the electrode laminate. In order to obtain an electrode laminate with less wrinkles and distortions, the following manufacturing methods for an electrode sheet or a sheet electrode have been disclosed.
[0003] For example, Patent Document 1 discloses an electrode sheet having a metal foil and a coated portion and an uncoated portion arranged on the metal foil, in which the coated portion has at least an electrode mixture layer containing an active material, the uncoated portion does not have the electrode mixture layer, and when the electrode sheet is viewed in a plan view in the thickness direction, the direction from the end of the coated portion to the end of the uncoated portion is defined as a first direction, and the direction perpendicular to the first direction is defined as a second direction, the uncoated portion has a notch extending in the second direction. Patent Document 1 discloses an electrode sheet capable of suppressing the occurrence of wrinkles in the uncoated portion, or an electrode sheet in which the occurrence of wrinkles is suppressed.
[0004] Patent Document 2 discloses a method for manufacturing a sheet electrode, which includes measuring the amount of curvature of a sheet electrode after a roll press in which an electrode active material is coated and dried on the surface of a current collector sheet, calculating the strain difference in the width direction of the sheet electrode using a specific calculation formula, determining warm straightening conditions from a correlation between the previously determined warm tensile properties of the current collector sheet and the strain difference, and straightening the sheet electrode to remove distortion under the determined warm straightening conditions. According to the method for manufacturing a sheet electrode in Patent Document 2, it is said that by straightening the sheet electrode to remove distortion under appropriate warm straightening conditions, problems of waviness and curvature on the surface of the sheet electrode can be eliminated, and a flat sheet electrode without distortion can be obtained. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2023-060558 A [Patent Document 2] Patent No. 3683134 Summary of the Invention [Problem to be solved by the invention]
[0006] In the roll press process for producing the electrode laminate, the metal current collector layer expands in response to the expansion of the electrode active material layer in the width direction during roll press, so no wrinkles are generated in the electrode laminate. However, immediately after roll press, the contraction stress (springback) of the metal current collector layer in the electrode laminate to return to its original size is greater than the contraction stress of the electrode active material layer, so wrinkles are generated.
[0007] In particular, in the manufacture of an all-solid-state battery that contains only a solid electrolyte as the electrolyte layer, the electrode laminate needs to be roll-pressed at a high pressure compared to a liquid-based battery that contains an electrolytic solution in the electrolyte layer, and the electrode laminate as a whole is designed to have low rigidity, so the problem of wrinkles due to roll pressing is significant.
[0008] In view of the above, an object of the present disclosure is to provide a method for producing an electrode laminate that can suppress the occurrence of wrinkles in the electrode laminate immediately after roll pressing. [Means for solving the problem]
[0009] The present disclosure achieves the above object by the following means.
[0010] (1) Both sides of the electrode laminate are sandwiched between metal plates, and roll pressing the electrode laminate sandwiched between the metal plates; A method for producing an electrode stack, comprising: The electrode laminate includes a metal current collector layer and an electrode active material layer, and The metal plate has a thickness of 100 μm or more and less than 1 mm. A method for manufacturing an electrode laminate. Effect of the Invention
[0011] According to the method for producing an electrode laminate of the present disclosure, it is possible to suppress wrinkles that occur immediately after roll pressing. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating an electrode laminate sandwiched between metal plates in a manufacturing method of an electrode laminate according to the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view for explaining the electrode laminate produced in Example 1. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, the embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the gist of the present disclosure. In addition, in the description of the drawings, the same elements are given the same reference numerals, and duplicated descriptions will be omitted.
[0014] <<Method for manufacturing electrode laminate>> The method for producing an electrode laminate according to the present disclosure includes: Sandwiching both sides of the electrode laminate between metal plates; and roll pressing the electrode laminate sandwiched between the metal plates; A method for producing an electrode stack, comprising: The electrode laminate includes a metal current collector layer and an electrode active material layer, and The metal plate has a thickness of 100 μm or more and less than 1 mm.
[0015] According to the method for producing an electrode laminate of the present disclosure, it is possible to suppress wrinkles that occur immediately after roll pressing.
[0016] Immediately after roll pressing, the contraction stress (springback) of the metal current collector layer in the electrode laminate trying to return to its original size is greater than the contraction stress of the electrode active material layer, so the electrode active material layer is pulled by the metal current collector layer, which is thought to cause wrinkles. The details of the presumed mechanism of wrinkle formation are described below.
[0017] It is considered that immediately after the start of the roll press, the electrode active material layer stretches in the width direction due to not only the surface pressure of the roll press but also the friction between the rolls of the roll press and the electrode active material layer. Then, during the roll press, it is considered that the metal current collector layer also stretches accordingly due to the surface pressure of the roll press and the friction between the electrode active material layer stretched by the roll press and the metal current collector layer.
[0018] Generally, the metal current collector layer has a larger Young's modulus than the electrode active material layer, and therefore, as the elongation increases, the difference between the contraction stress of the metal current collector layer and that of the electrode active material layer increases. The greater the difference in the contraction stress, the more the electrode active material layer is pulled by the metal current collector layer, and the more likely wrinkles are to occur.
[0019] The present inventors have focused on reducing the elongation of the electrode active material layer, thereby reducing the elongation of the metal current collector layer due to friction with the electrode active material layer and reducing the shrinkage stress of the metal current collector layer. Specifically, when the electrode laminate is sandwiched between highly rigid metal plates (e.g., SUS plates) and roll-pressed, the elongation of the electrode active material layer due to the frictional force transmitted from the rolls of the roll press to the electrode active material layer is reduced, and this reduces the elongation of the metal current collector layer, thereby reducing the difference between the shrinkage stress of the metal current collector layer and the shrinkage stress of the electrode active material layer, and thus suppressing the occurrence of wrinkles.
[0020] <Metal plate pinching> The method for producing an electrode laminate according to the present disclosure includes sandwiching both sides of an electrode laminate between metal plates.
[0021] FIG. 1 is a schematic diagram showing one embodiment of sandwiching an electrode laminate between metal plates in the manufacturing method of an electrode laminate of the present disclosure, but the present invention is not limited to this embodiment.
[0022] The electrode laminate 6 in Fig. 1 has electrode active material layers 5 on both sides of a metal current collector layer 1. Furthermore, the electrode active material layer 5 has a negative electrode active material layer 2, a solid electrolyte layer 3, and a positive electrode active material layer 4 laminated in this order from the side closest to the metal current collector layer 1. The electrode laminate 6 is sandwiched between metal plates 7 from the outside of the positive electrode active material layers 4 on the upper and lower surfaces, thereby obtaining an electrode laminate 6 sandwiched between the metal plates 7. The metal plates sandwiching the upper and lower surfaces may be the same type of metal plates, or different types of metal plates may be used.
[0023] <Roll Press> The manufacturing method of the electrode laminate of the present disclosure includes roll pressing the electrode laminate sandwiched between metal plates.
[0024] The electrode laminate sandwiched between the metal plates on both sides may be roll-pressed at a predetermined line pressure and temperature. After the roll-press, the electrode laminate sandwiched between the metal plates can be recovered by removing the metal plates.
[0025] The linear pressure of the roll press is not particularly limited, but may be 1 to 30 ton / cm, preferably 2 to 20 ton / cm, more preferably 4 to 10 ton / cm, from the viewpoint of densifying the electrode active material layer. The linear pressure of the roll press is not particularly limited, but may be 1 ton / cm or more, 2 ton / cm or more, or 4 ton / cm or more, and may be 30 ton / cm or less, 20 ton / cm or less, or 10 ton / cm or less.
[0026] The temperature of the roll press is not particularly limited, but may be 100°C or more, 140°C or more, or 160°C or more, and may be 240°C or less, 200°C or less, or 180°C or less.
[0027] <Electrode laminate> The electrode laminate of the present disclosure includes a metal current collector layer and an electrode active material layer. The electrode laminate may also include a solid electrolyte layer.
[0028] Metal current collector layer The metal current collector layer is not particularly limited, and may be any suitable metal that can be used in lithium ion batteries. For example, it may be aluminum, copper, SUS, nickel, iron, titanium, carbon, or the like. It may also be a metal such as aluminum, copper, SUS, nickel, iron, or titanium that is coated, plated, or vapor-deposited with carbon.
[0029] The shape of the metal current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.
[0030] <Electrode active material layer> The electrode active material layer may include, but is not limited to, at least one of a positive electrode active material layer and a negative electrode active material layer. The electrode active material layer may be formed on one or both sides of the metal current collector layer, but is not limited to.
[0031] (Cathode active material layer) The positive electrode active material layer contains at least a positive electrode active material, and preferably further contains a solid electrolyte described below. In addition, it may contain additives used in the positive electrode active material layer of an all-solid-state battery, such as a conductive assistant or a binder, depending on the intended use or purpose.
[0032] The material of the positive electrode active material is not particularly limited. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), LiCO 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li 1+x Mn 2-x-y M y Li-Mn spinel substituted with different elements having a composition represented by O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn), LiNi x Co y Al z The oxygen saturation agent may be, but is not limited to, O2(NCA), etc.
[0033] The conductive additive is not particularly limited, and may be, for example, a carbon material such as VGCF (Vapor Grown Carbon Fiber) and carbon nanofiber, a metal, or the like, but is not limited thereto.
[0034] The binder is not particularly limited. For example, the binder may be, but is not limited to, a material such as polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC), butadiene rubber (BR), or styrene butadiene rubber (SBR), or a combination thereof.
[0035] (Negative electrode active material layer) The negative electrode active material layer contains at least a negative electrode active material, and preferably further contains a solid electrolyte described below. In addition, it may contain additives used in the negative electrode active material layer of an all-solid-state battery, such as a conductive assistant or a binder, depending on the intended use or purpose.
[0036] The material of the negative electrode active material is not particularly limited, and is preferably capable of absorbing and releasing metal ions such as lithium ions. For example, the negative electrode active material may be, but is not limited to, an alloy-based negative electrode active material, a carbon material, lithium titanate (LTO), etc.
[0037] The alloy-based negative electrode active material is not particularly limited, and examples thereof include Si alloy-based negative electrode active materials and Sn alloy-based negative electrode active materials. The Si alloy-based negative electrode active material includes silicon, silicon oxide, silicon carbide, silicon nitride, and solid solutions thereof. The Si alloy-based negative electrode active material can include elements other than silicon, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Sn, Ti, and the like. The Sn alloy-based negative electrode active material can include tin, tin oxide, tin nitride, and solid solutions thereof. The Sn alloy-based negative electrode active material can include elements other than tin, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Ti, Si, and the like. Among these, the Si alloy-based negative electrode active material is preferred.
[0038] The carbon material is not particularly limited, and examples thereof include hard carbon, soft carbon, graphite, and the like.
[0039] As for the solid electrolyte, conductive assistant, binder and other additives used in the negative electrode active material layer, those explained in the above section "(Positive electrode active material layer)" can be appropriately used.
[0040] (Solid electrolyte layer) The solid electrolyte layer includes at least a solid electrolyte. The solid electrolyte is not particularly limited, and any material that can be used as a solid electrolyte in an all-solid-state battery can be used. For example, the solid electrolyte may be, but is not limited to, a sulfide solid electrolyte, an oxide solid electrolyte, or a polymer electrolyte.
[0041] Examples of sulfide solid electrolytes include, but are not limited to, sulfide-based amorphous solid electrolytes, sulfide-based crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2 (Li 13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.
[0042] An example of an oxide solid electrolyte is Li7La3Zr2O 12 , Li 7-x La3Zr 1-x Nb x O 12 , Li 7-3x La3Zr2Al x O 12 , Li 3x La2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4-x N x (LiPON), but is not limited to these.
[0043] Examples of the polymer electrolyte include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), and copolymers thereof.
[0044] The solid electrolyte may be glass or crystallized glass (glass ceramic). The solid electrolyte layer may contain a binder, etc., as necessary, in addition to the above-mentioned solid electrolyte. Specific examples are the same as the "binders" listed in the above "(positive electrode active material layer)", and so a description thereof will be omitted here.
[0045] The lithium ion battery including the electrode laminate produced by the method of the present disclosure may be a liquid battery containing an electrolytic solution as the electrolyte layer, or may be a solid battery having a solid electrolyte layer as the electrolyte layer. In the present disclosure, a "solid-state battery" means a battery using at least a solid electrolyte as the electrolyte, and therefore a solid-state battery may use a combination of a solid electrolyte and a liquid electrolyte as the electrolyte. The solid-state battery of the present disclosure may also be an all-solid-state battery, i.e., a battery using only a solid electrolyte as the electrolyte.
[0046] <Metal plate> The metal plate has a thickness of not less than 100 μm and not more than 1 mm.
[0047] The material of the metal plate is not particularly limited, but from the viewpoint of the rigidity of the metal plate, it is preferable to use stainless steel (SUS), iron (Fe), or the like.
[0048] The thickness of the metal plate is preferably 100 μm or more from the viewpoint of suppressing wrinkles in the electrode laminate immediately after roll pressing, and is preferably less than 1 mm from the viewpoint of workability. EXAMPLES
[0049] The present disclosure will be described in more detail with reference to the following examples, but the scope of the present disclosure is not limited to these examples.
[0050] Example 1 <Preparation process; negative electrode active material layer> A negative electrode composite material for an all-solid-state battery (e.g., an LTO negative electrode composite material) was applied to both sides of a metal foil (e.g., carbon-coated Al foil 17 μm) serving as a negative electrode current collector, and then dried to obtain a negative electrode active material layer formed on both sides of the metal current collector layer.
[0051] <Preparation process; solid electrolyte layer and positive electrode active material layer> A solid electrolyte mixture for an all-solid-state battery was applied to one side of a metal foil substrate (e.g., Al foil 15 μm thick) and dried to obtain a solid electrolyte layer formed on one side of the substrate. Similarly, a positive electrode mixture (e.g., NCA positive electrode mixture) was applied to another substrate and dried to obtain a positive electrode active material layer formed on one side of the substrate.
[0052] <Preparation step: Electrode laminate obtained by laminating a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer> A solid electrolyte layer formed on one side of a substrate was laminated on each side of the negative electrode active material layer formed on both sides of the negative electrode current collector, and the negative electrode active material layer and the solid electrolyte layer were bonded by roll pressing (pressure 20 kN). Then, only the substrate of each solid electrolyte layer was peeled off. Furthermore, a positive electrode active material layer formed on one side of a substrate was laminated on each side of the solid electrolyte layer laminated on both sides of the negative electrode active material layer, and the solid electrolyte layer and the positive electrode active material layer were bonded by roll pressing (pressure 20 kN). Then, only the substrate of each positive electrode active material layer was peeled off to prepare an electrode laminate. The thickness of the electrode laminate was 180 μm.
[0053] <Pressing process> Both sides of the electrode laminate obtained in the preparation step were sandwiched between SUS (stainless steel) plates (thickness 100 μm), and roll pressed under conditions of a temperature of 170° C. and a linear pressure of 4.5 ton / cm.
[0054] <Removal process> The SUS plates were removed from the pressed electrode laminate with both sides sandwiched between them to obtain electrode laminate A shown in FIG. 2. The wrinkle height and wrinkle cycle length of electrode laminate A were measured using a height / flatness measuring device HM-1000 (manufactured by Keyence Corporation). The wrinkle height of electrode laminate A was 0.19 mm, and the wrinkle cycle length was 18 mm. Here, the wrinkle height is the difference between the maximum and minimum values of the amplitude due to the wrinkles in the measurement area, and the wrinkle cycle length is the length from the minimum value of the wrinkle height in the measurement area to the minimum value.
[0055] Comparative Example 1 Except that in the pressing step of Example 1, two SUS plates (thickness 50 μm) were sandwiched on each side of the electrode laminate, an electrode laminate a after pressing was obtained in the same manner as in Example 1. The wrinkle height of the electrode laminate a was 0.28 mm, and the wrinkle periodic length was 9.5 mm.
[0056] Comparative Example 2 In the pressing step of Example 1, both sides of the electrode laminate were sandwiched between SUS plates (thickness 1 mm) and roll pressing was attempted. However, the gap between the rolls was insufficient, and roll pressing was not possible.
[0057] Table 1 shows the wrinkle heights and wrinkle periods of the electrode laminates produced in Example 1 and Comparative Examples 1 and 2.
[0058] [Table 1]
[0059] In Example 1, the electrode active material layer was sandwiched between SUS plates having a larger thickness, i.e., SUS plates having a higher rigidity, compared to Comparative Example 1, and then roll pressed. As a result, both the wrinkle height and the wrinkle cycle length were reduced. This is considered to be because the elongation of the electrode active material layer due to the frictional force transmitted from the rolls of the roll press to the electrode active material layer was reduced.
[0060] Although preferred embodiments of the methods for manufacturing electrode stacks of the present disclosure have been described, those skilled in the art will recognize that modifications are possible without departing from the scope of the claims. [Explanation of symbols]
[0061] 1 Metal collector layer 2 Negative electrode active material layer 3 Solid electrolyte layer 4 Cathode active material layer 5 Electrode active material layer 6 Electrode laminate 7 metal plate
Claims
[Claim 1] Sandwiching both sides of the electrode laminate between metal plates; and roll pressing the electrode laminate sandwiched between the metal plates; A method for producing an electrode stack, comprising: The electrode laminate includes a metal current collector layer and an electrode active material layer, and The metal plate has a thickness of 100 μm or more and less than 1 mm. A method for manufacturing an electrode laminate.
Citation Information
Patent Citations
Electrode sheet
JP2023060558A
Sheet electrode manufacturing method
JP3683134B2